(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2024)
Cultivating seaweed presents an opportunity to enhance the livelihoods of the inhabitants of St. Martin’s Island inhabitants. This research investigates the suitability of the island’s coastal waters for seaweed cultivation, taking into account variations in physicochemical factors in different seasons. The water temperature and salinity at various locations ranged from 24.22ºC to 27.64ºC and 23.8 to 33.76 psu, respectively. pH remained relatively constant throughout the year, fluctuating between 7.71 and 8.22. Dissolved oxygen levels were highest during the dry, cooler winter season (6.47±0.21 ppm) and lowest during the monsoon season (4.96±0.09 ppm). Electrical conductivity (EC) ranged from 39.00 mS/cm to 53.46 mS/cm, while total dissolved solids (TDS) varied between 20.35 and 27.90 g/l. Water clarity was at its peak during the dry, cooler winter season, averaging 4.14 meters. This investigation confirms the feasibility of year-round seaweed cultivation in the coastal waters around St. Martin’s Island. In our study comparing cultivation methods for Padina gymnospora during the dry, cool winter season, the long-line approach resulted in a higher daily weight gain compared to the floating net method. This trend extended to growth rates by length, with the long-line method demonstrating a 5.09% daily growth and the floating net method showing 4.46%. However, net biomass production was 289.32 g/m² for the long-line method and 381.28 g/m² for the floating net method. Furthermore, the Cost-Benefit Ratio values for the long-line and floating net methods were 2.57 and 3.27, respectively. These findings affirm the viability of cultivating Padina gymnospora in coastal waters using the floating net method. Biodivers. Conserv. Bioresour. Manag. 2024, 10(1): 1-14